Chromatographic ECD fingerprints combined with a chemometric method used for the identification of three light-coloured unifloral honeys. Issue 19 (7th October 2015) - Zhao, Jing; Cheng, Ni; Xue, Xiaofeng; Wu, Liming; Zhu, Xiaohong; Cao, Wei
<x xml:space="preserve">Abstract</x> HPLC-ECD fingerprints of linden honey samples.